All by myself, alone eaudiobook - Higgins Clark, Mary (Simon & Schuster Audio, 2017)
From the Queen of Suspense and #1 New York Times bestselling author comes a thrilling mystery aboard a luxurious but deadly cruise. Fleeing the disastrous and humiliating last-minute arrest of her fiancé on the eve of their wedding, Celia, an expert on gems and jewelry, is hoping to escape from reality on a glamorous cruise ship. But it is not to be. On board in the most luxurious suite is the elderly and world-famous Lady Emily Harworth. Immensely wealthy, Lady Em is the owner of a priceless emerald necklace that she intends to leave to the Smithsonian on her death. Three days later Lady Em is found dead—and the necklace is missing. Is it the work of her apparently devoted secretary, or her lawyer-executor, both of whom she had invited on board for the cruise? Celia, with the help of her new friends Willy and Alvirah Meehan—who are splurging on their wedding anniversary—sets out to find who the killer is, not realizing that she may have put a target on her back.